Phytochemical profiles and biological activity of Myrsine africana L.: a comprehensive review - Moges, Getaneh Worku; Manahelohe, Gizachew Mulugeta; Assege, Melesse Ababay; Tasew, Banchamlak Sewachen; Molla, Desilal Kokebie; Belew, Aderaw Anteneh (Frontiers in Pharmacology, 2025)
Myrsine africana L. is a member of the Myrsinaceae family, which encompasses more than 1,000 species and 35 genera predominantly found in tropical and subtropical regions. This plant is abundant in Africa and Asia, and has been traditionally utilized for its aromatic properties in tea, spices, appetizers, carminatives, and flavoring agents. Despite its wide-ranging applications, a comprehensive review of its phytochemical potential and biological effects has not yet been conducted. This study aims to fill that gap by reviewing the phytochemical composition and biological activities of M. africana. Literature was gathered using databases such as Google Scholar, PubMed, Scopus, and Web of Science. The wide range of uses of M. africana can be attributed to its rich phytochemicals, including alkaloids, flavonoids, phenols, terpenoids, and saponins. Among its significant biological activities, M. africana is known for its anti-inflammatory and antioxidant properties. Furthermore, it shows potential in antispasmodic, antityrosinase, antibacterial, anti-aging, and anticancer applications. Additionally, it is used to treat conditions, such as malaria, helminthosis, wounds, tuberculosis, and gastrointestinal complications. Some of the isolated compounds from different parts of M. africana include methylvilangin (11), methylanhydrovilangin (12), 2-hydroxychrysophanol (13), myrsinene (25), myrsigenin (26), myrsininone A (27), myrsininone B (28), and myrsinoside B (30), as well as various other flavonoid compounds. This review aims to systematically explore the phytochemical profiles and associated biological activities of M. africana, highlighting key compounds and their pharmacological implications. By bringing together information, it emphasizes the potential of M. africana in drug discovery and future research.